Investigation of the influence of the impedance surface on the propagation of acoustic waves - Запорожець, О. І.; Токарев, В. І. (Proceedings of National Aviation University (archive), 2002)
A new solution of the problem of propagation of sound along the impedance surface using the Helmholtz equation and the corresponding boundary condition is considered. The resulting solution is compared with the known theoretical and experimental data of propagation of sound along the reflecting impedance surface